2011
DOI: 10.1002/j.1556-6678.2011.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Rural High School Students Go to Find Information About Their Futures?

Abstract: Using data from a national study of rural high school youth, the authors examined where students go to receive information about their futures and which sources are most helpful. Results indicated that students in rural and low‐income schools were more likely to report going to teachers and found teachers to be most helpful compared with students in small town and higher income schools. Patterns of differentiation were also found on the basis of gender, ethnicity, and grade level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…In addition, parents in rural areas have lower postsecondary educational attainment and educational expectations for their children than parents in nonrural areas (Provasnik et al, 2007; Roscigno & Crowley, 2001; Roscigno et al, 2006). Furthermore, rural youth are more likely than nonrural youth to experience a narrow school curriculum and limited access to career counseling and college preparatory programs (Graham, 2009; Griffin, Hutchins, & Meece, 2011; Lapan, Tucker, Kim, & Koscuilek, 2003; Monk, 2007; Provasnik et al, 2007). A substantial body of evidence suggests that these precollege factors (i.e., family income, parents' education and educational expectations, and academic preparation) predict youth's college enrollment, persistence, and completion (Adelman, 2006; Adelman, Daniel, Berkovits, & Owings, 2003; Attewell, Heil, & Reisel, 2011; Bozick, 2007; Goldrick-Rab, 2006; Goldrick-Rab & Pfeffer, 2009).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…In addition, parents in rural areas have lower postsecondary educational attainment and educational expectations for their children than parents in nonrural areas (Provasnik et al, 2007; Roscigno & Crowley, 2001; Roscigno et al, 2006). Furthermore, rural youth are more likely than nonrural youth to experience a narrow school curriculum and limited access to career counseling and college preparatory programs (Graham, 2009; Griffin, Hutchins, & Meece, 2011; Lapan, Tucker, Kim, & Koscuilek, 2003; Monk, 2007; Provasnik et al, 2007). A substantial body of evidence suggests that these precollege factors (i.e., family income, parents' education and educational expectations, and academic preparation) predict youth's college enrollment, persistence, and completion (Adelman, 2006; Adelman, Daniel, Berkovits, & Owings, 2003; Attewell, Heil, & Reisel, 2011; Bozick, 2007; Goldrick-Rab, 2006; Goldrick-Rab & Pfeffer, 2009).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…Even though the students in this study demonstrated better knowledge about the PT profession than they did about the OT profession, this did not translate into increased interest in the PT profession as a career choice. Many factors have been shown to influence career aspirations, including race and ethnicity; socioeconomic status; gender; the influence of friends, peers, teachers, and parents; and intrinsic personal factors (Griffin, Hutchins, & Meece, 2011;Howard et al, 2011). The interactions between these factors can be complex and dynamic.…”
Section: Career Choicesmentioning
confidence: 99%
“…However, studies of parents have addressed expectations of adolescence in general (i.e., as a stormy and stressful period of life), not specific milestones in adolescents' lives, such as the middle school transition. Understanding parents' expectations for the move to middle school may be particularly important, given that rural adolescents look to their parents, more so than to peers or teachers, for information and advice about schooling experiences (Griffin, Hutchins, & Meece, 2011).…”
Section: Importance Of the Problemmentioning
confidence: 99%